Analysis of finite antenna arrays in the presence of arbitrary electromagnetic structures - Ludick, D.; Davidson, David; Jakobus, U. (2015)
© 2015 IEEE. This work considers the analysis of finite antenna arrays in the presence of arbitrary electromagnetic structures, e.g. a focal plane array illuminating a parabolic dish antenna, or an antenna array located above a finite sized ground plane. The fast solution approach applies domain decomposition where the finite array is considered as one domain and the remainder of the geometry as the other. Two Method-of-Moment (MoM) based strategies will be considered to analyse the coupling between the domains, viz. The Numerical Greens Function Method (NGF) as well as an Iterative Field Bouncing (IFB) scheme. These methods will be compared in terms of accuracy and runtime when used to analyse a bow-tie antenna array situated above a finite size ground plane.